Validation of Daily Rainfall Based on Global Satellite Mapping Of Precipitation (Gsmap) Data with Observation Data in The Bali Region - Duwanda, I Gusti Agung Made; Sukarasa, I Ketut (BULETIN FISIKA; Vol 23 No 2 (2022): BULETIN FISIKA August EditionDO - 10.24843/BF.2022.v23.i02.p05, 2021)
Research has been done on the validation of rainfall based on Global Satellite Mapping of Precipitation GSMaP data with observation data in the Bali area. The method used in this research is Pearson correlation, root mean square error (RMSE), and mean square error (MBE). This study aims to validate GSMaP rainfall data with observations in the Bali area. In general, GSMaP rainfall data tends to have a smaller value than observation data, but has almost the same data pattern in each area with rainfall patterns that occur from November to March. The study shows a strong positive correlation value (> 0.5), where in the Ngurah Rai area the value of = 0.889 with =0.558 and = 0.061 , in Negara the value of = 0.887 with = 0.595 and = 0.049, and in Denpasar area the value of = 0.879 dengan = 0.444 dan = 0.058 . This shows that GSMaP satellite data is quite valid and can be used especially in 3 observation areas, namely Ngurah Rai, Negara, and Denpasar.